Ethynilestradiol 20 mcg plus Levonorgestrel 100 mcg: Clinical Pharmacology - Stefano Lello; Andrea Cavani (International Journal of Endocrinology)
Estroprogestins (EPs) are combinations of estrogen and progestin with several actions on women’s health. The different pharmacological composition of EPs is responsible for different clinical effects. One of the most used low-dose EP associations is ethinylestradiol 20 mcg plus levonorgestrel 100 mcg in monophasic regimen (EE20/LNG100). This review summarizes clinical pharmacology, cycle control, and effects on lipid and glucose metabolism, coagulation, body weight/body composition, acne, and sexuality of EE20/LNG100. Overall, EE20/LNG100 combination is safe and well tolerated, and in several studies the incidence of adverse events in the treated group was comparable to that of the placebo group. Cycle control was effective and body weight/body composition did not vary among treated and untreated groups in most studies. The EE20/LNG100 combination shows mild or no effect on lipid and glucose metabolism. Lastly, EE20/LNG100 is associated with a low risk of venous thromboembolism (VTE). In conclusion, in the process of decision making for the individualization of EPs choice, EE20/LNG100 should be considered for its favorable clinical profile.